Imagined sovereignties : the power of the people and other myths of the modern age - Olson, Kevin (Cambridge University Press, 2016)
"Movements like the Arab Spring, Occupy Wall Street, and the Tea Party embody some of our deepest intuitions about popular politics and 'the power of the people'. They also expose tensions and shortcomings in our understanding of these ideals. We typically see 'the people' as having a special, sovereign power. Despite the centrality of this idea in our thinking, we have little understanding of why it has such importance. Imagined Sovereignties probes the considerable force that 'the people' exercises on our thought and practice. Like the imagined communities described by Benedict Anderson, popular politics is formed around shared, imaginary constructs rooted in our collective imagination. This book investigates these 'imagined sovereignties' in a genealogy traversing the French Enlightenment, the Haitian Revolution, and nineteenth-century Haitian constitutionalism. It problematizes taken-for-granted ideas about popular politics and provokes new ways of imagining the power of the people"--